Representação do mundo rural: identidades em construção em um espaço de conflitos (Campo Florido) - MACHADO, Flávia Pereira (2006)
The social transformations, politics, economical and cultural impelled by the expansion of the modernity" "project to Brazil imposed the need of a realignment of the agrarian social world starting from the process of agricultural modernization. New identities, subjects and representations appear or they are visibilities in the breast of this process making possible the perception of the complexity of the work relationships, sociability and production that delineate the rural world. Elements of the "modern life" intersect with values and "traditional" senses in the emergency of a new one rural Brazilian, making possible the construction of differentiated images of the field and of the city, that some times converge her, other times oppose. The search of explanations for the contrasts among these two universes (rural and urban) they imposed the identification of the field as place of the "delay", and the city as locus of the "modernity", of the "progress", or even of a continuity of the city in the field with the urbanization process of this. In order to we overcome these visions dichotomists, we challenged ourselves to the interpretation of the constitution of multiple identities and representations concerning the rural world starting from the daily of fight and work, of the life experiences and speeches built by these new insurgent subjects: seated rural originating from of the fight by the earth. In the construction of a social and cultural "place" in the extent of the modernization process the subjects establish several negotiation strategies among the "modern" and the "traditional", the rural and the urban in the delimitation of a new symbolic universe, constituting new identities (personal and collective). In this sense, our proposal if it rules in the process of statement identities be noticed in the different speeches, representations and strategies of material and cultural survival built by these subjects in his/her daily one.